Hans Jonas’s reflections on cosmogony, theodicy and his argument for God’s existence: a possible enrichment for Christian theology in dialogue with modern natural science - Settimo, Luca (2022)
The famous Jewish thinker Hans Jonas has written extensively across different philosophical topics and is particularly renowned for his work in ethics. Throughout his extensive career he has also published many theological reflections; some of these, however, are not well known given that, up until now, they have never been translated into English. In this dissertation, I will aim to provide a fuller, more comprehensive understanding of Jonas’s theological reflections – in particular those concerning cosmogony, theodicy and his argument for God’s existence. I will argue that these three areas are strictly related to his ethical project, given their powerful implications for human responsibility in protecting the sacredness of all life and the care of creation. Moreover, I will reveal that Jonas’s philosophical-theological reflections on this topic complement his understanding of natural science. Jonas is critical of reductionist/determinist approaches in modern science which have the effect of ‘desacralising’ the natural world; thus, his philosophical-theological proposal acts as the antidote for this flawed scientific perspective. Given these reasons, I strongly contend that Jonas’s philosophical-theological contributions can foster a fruitful dialogue with modern natural science (especially in relation to laws of nature and the emergence of life through cosmic evolution) and can enrich Christian theology. During my analysis of Jonas’s theological reflections I will outline the existence of several notable ‘dialectical tensions’ in his view of God (whom he concomitantly describes as a transcendent and immanent Being). I will therefore also critically evaluate Jonas’s theology and explore further some contradictions also found between his teachings and Christian orthodoxy. I shall then attempt (using the correct theological framework) to provide some correctives on these problematic issues, with the aim of remaining faithful to Jonas’s perspective, while remaining compatible with Christian theology. Finally, I explore how other scholars (both Jonas’s contemporaries and those preceding him) may have influenced and motivated him in his theological reflections: this exercise is key in order to fully understand, appreciate and position Jonas’s perspective in relation to other philosophical-theological schools.